Análisis del cambio de tecnología en los transformadores de corriente para mejorar la eficiencia de registro de las mediciones semi-directas e indirectas para clientes especiales dentro del área de concesión de CNEL EP Guayaquil. - Ibarra Menéndez, Alex Samuel (2019)
The present project is based on the analysis of the different types of current transformers used in semi direct and indirect measurements in the concession area of CNEL EP U.N. Guayaquil, a new type of technology will be studied in transformers of current as are extended range. It will detail the elements that take part in the measuring systems, their connections and form of registration of the consumption of the special clients of this distributor. In this work, the management and installation of a measurement equipment with discrete-range cascade current transformers is demonstrated with another one of a different technology, such as those of extended range that are installed in a special industrial rate customer with demand, for Consequence is established based on contrast of records and calculations, the percentage accuracy of both measurement systems. In addition, it details the installation of an energy quality analyzer equipment to perform tests and compare the records with the extended range and discrete range measurements. Finally we show the results obtained from the tests and calculations made in tables and diagrams developed, according to the ranges in percentage of accuracy that allows us to conclude that the technology change of this equipment to one of type extended range it provides more precision for the energy record, benefiting the distributor.